The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acsomega.0c00509
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Regulated α-Oxygenation of α-Bromocarbonyl Compounds Promoted Using 2-Aryl-1,3-dimethylbenzimidazolines and Air

Abstract: A debrominative oxygenation protocol has been developed for the conversion of α-bromo-α,α-dialkyl-substituted carbonyl compounds to their corresponding α-hydroxy analogues. For example, stirring a solution of α-bromoisobutyrophenone and 2-aryl-1,3-dimethylbenzimidazoline (BIH-Ar) at room temperature under an air atmosphere leads to the efficient formation of α-hydroperoxyisobutyrophenone, which can be converted to α-hydroxyisobutyrophenone using Me2S reduction. In contrast, reaction of α-bromoacetophenone unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 138 publications
2
19
0
Order By: Relevance
“…On the other hand, 4a is not produced when the reaction is carried out under a N 2 atmosphere (entry 3). It is interesting to note that the dark reaction of α-bromoisobutyrophenone with 1g is significantly decelerated when a N 2 atmosphere is employed, but the rate of the photoreaction of 2a with 1a under N 2 is not significantly decreased (compare entry 3 to entries 1 and 2). A similar trend is seen in the reaction of α-benzylphenone 2b ( E 1/2 red = −1.48 V vs SCE, see Table S1) where oxidation product 4b is not formed when a N 2 atmosphere is used (entries 4, 5, and 6).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, 4a is not produced when the reaction is carried out under a N 2 atmosphere (entry 3). It is interesting to note that the dark reaction of α-bromoisobutyrophenone with 1g is significantly decelerated when a N 2 atmosphere is employed, but the rate of the photoreaction of 2a with 1a under N 2 is not significantly decreased (compare entry 3 to entries 1 and 2). A similar trend is seen in the reaction of α-benzylphenone 2b ( E 1/2 red = −1.48 V vs SCE, see Table S1) where oxidation product 4b is not formed when a N 2 atmosphere is used (entries 4, 5, and 6).…”
Section: Resultssupporting
confidence: 92%
“…Reaction of 2a with 1g was first conducted under the conditions [dimethyl sulfoxide (DMSO), room temperature, air atmosphere] which would have led to complete conversion of α-bromoisobutyrophenone to the corresponding α-hydroperoxyphenone 5a (see Scheme ). However, 1 H NMR analysis of the product mixture showed that this process generates a trace of isobutyrophenone 3a and only a small quantity of α-hydroxyisobutyrophenone 4a . This observation clearly suggests that 2a and 1g do not efficiently participate in a dark SET–HAT reaction, like the one occurring between α-bromoisobutyrophenone and 1g (see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [11–14] Owing to their significant importance in biology, they have attracted the considerable attention of synthetic organic chemists. However, direct incorporation of a hydroxy group in a stereoselective fashion at the α‐position of carbonyls is very challenging, and reports are limited [15–17] …”
Section: Introductionmentioning
confidence: 99%
“…The first one is demonstrated but the second is questionable. 26 In this paper we show the evolution over time of the NMR spectra of carefully purified samples of DMBI-H as solution in the processing solvent. We characterize and isolate the most relevant byproduct thus formed and we evaluate the impact of its presence in DMBI-H/P(NDI2OD-T2) blends.…”
mentioning
confidence: 99%